Comparing an ACO algorithm with other heuristics for the single machine scheduling problem with sequence-dependent setup times - Gagné, C; Price, W L; Gravel, M (The Journal of the Operational Research Society, 2002)
We compare several heuristics for solving a single machine scheduling problem. In the operating situation modelled, setup times are sequence-dependent and the objective is to minimize total tardiness. We describe an Ant Colony Optimization (ACO) algorithm having a new feature using look-ahead information in the transition rule. This feature shows an improvement in performance. A comparison with a genetic algorithm, a simulated annealing approach, a local search method and a branch-and-bound algorithm indicates that the ACO that we describe is competitive and has a certain advantage for larger problems.